Contemporary issues in conversation analysis: Embodiment and materiality, multimodality and multisensoriality in social interaction - Mondada, Lorenza (Journal of pragmatics, 2019)
This paper reviews some current trends characterizing the specific perspective of ethnomethodologically inspired conversation analysis on the situated organization of action. It also discusses contemporary challenges represented within this paradigm by the study of materiality and embodiment in social interaction. In order to further elaborate on the nexus between action, bodies, and materiality, I show on the basis of an empirical exemplary situation, how research on multimodality – that is, on the diversity of resources that participants mobilize to produce and understand social interaction as publicly intelligible action, including language, gesture, gaze, body postures, movements, and embodied manipulations of objects – can be further expanded by considering not only embodied resources for interacting but also embodied practices for sensing the world in an intersubjective way. •The paper discusses current state of the art in multimodal CA.•Recent expansions of multimodal analysis concern the body in its entirety, materiality, and ecology.•Situated action shapes the relevant material aspects of objects in interaction.•Material features are not only talked about and seen, but also sensed.•Multimodality can be further expanded to consider multisensoriality.